Physiological Study Comprising the Sequelae of Magnetic Radiation on Human - Wissam Sajid Hashim1, Azal Hamoody Jumaa2, Noor Thamer Alsaadi 1, Ayad Gaber Arean1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The sequelae of magnetic radiation of the towers of cellular phones were evaluated in this study depending upon a random social volunteer human male samples of ages 25 – 50 years and they were dwelling in houses close to the towers of cellular phones of distances not more than 150 miters far. The samples of these people were labelled as “Subjected”. Seventy five samples of blood were gained on a base of ages as twenty five from ages 25 – 30, twenty five from ages 35 – 40, and twenty five from ages 45 – 50 in addition to seventy five samples of people who did not dwell close to the towers and of the same previous pattern of ages and their samples were labelled as “Non subjected”. The results have demonstrated a significant elevation in transaminases (AST , ALT), blood calcium (Ca++), blood potassium (K+), total serum cholesterol (TSCH), triacylglycerols (TAGs), very low density lipoprotein (VLDL), and low density lipoprotein (LDL) .